2019
DOI: 10.1038/s41467-018-08015-x
|View full text |Cite
|
Sign up to set email alerts
|

SREBP-dependent lipidomic reprogramming as a broad-spectrum antiviral target

Abstract: Viruses are obligate intracellular microbes that exploit the host metabolic machineries to meet their biosynthetic demands, making these host pathways potential therapeutic targets. Here, by exploring a lipid library, we show that AM580, a retinoid derivative and RAR-α agonist, is highly potent in interrupting the life cycle of diverse viruses including Middle East respiratory syndrome coronavirus and influenza A virus. Using click chemistry, the overexpressed sterol regulatory element binding protein (SREBP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(288 citation statements)
references
References 68 publications
11
277
0
Order By: Relevance
“…28 Others found IAV replication was dependent on lipid metabolism. 160 However, in our hands, inhibitors of lipid metabolism were effective only in vitro. 28 We also identified BEZ235, a dual PI3K/mTOR inhibitor.…”
Section: Epithelial Metabolic Reprogramming By Influenzamentioning
confidence: 62%
“…28 Others found IAV replication was dependent on lipid metabolism. 160 However, in our hands, inhibitors of lipid metabolism were effective only in vitro. 28 We also identified BEZ235, a dual PI3K/mTOR inhibitor.…”
Section: Epithelial Metabolic Reprogramming By Influenzamentioning
confidence: 62%
“…ACE2 expression was reported to be upregulated after infection of various viruses [19]. Here, we examined the transcriptome of cells originated from human lung and found that 24-h infection of SARS-CoV-2, but not MERS-CoV [20] which does not use ACE2 as cell receptor, led to enhanced ACE2 expression ( Fig. 1b), probably accelerating replication and spread of the coronavirus.…”
Section: Ace2 Expression Was Enhanced By Sars-cov-2 Infectionmentioning
confidence: 80%
“…In this regard, the results of a study revealed that influenza infection could induce fatty acid biosynthesis and cholesterol metabolism in human lung basal epithelial tumor cells [87]. Since SREBPs are thoroughly identified as stimulators of expression of many genes involved in lipid and sterol biosynthesis, including fatty acid synthase [102][103][104], their upregulation by the influenza virus (through induction of mTORC1 signaling, as discussed earlier) may logically explain the increased rate of lipogenesis [105]. A coincidence between increased fatty acid synthesis and a decline in fatty acid β-oxidation has been found during influenza infection, which is attributed to a variety of mechanisms directly or indirectly related to viral replication.…”
Section: Lipid Metabolismmentioning
confidence: 93%
“…Studies have shown that these factors can play a variety of roles, such as energy supply and post-translational protein modification, as well as in the propagation of various groups of viruses such as influenza viruses. A study has shown that the AM580 compound, which is a retinoid derivative, inhibits SREBP-linked pathways, and it has antiviral activity against influenza A and coronavirus in vitro and in vivo [105].…”
Section: Novel Therapeutic Approaches By Targeting Metabolic Pathwaysmentioning
confidence: 99%